MODERN VIEW TO OPTIMIZATION OF DIAGNOSTICS OF PARKINSON'S DISEASE - Daminova Hilola Maratovna (Journal of Medical Genetics and Clinical Biology, 2024)
Parkinsonism is one of the most significant problems of clinical neurology, both due to its high prevalence in the world's populations and due to the significant disability of patients. The work analyzes the diagnosis of Parkinson's disease (as well as other neurodegenerative diseases) at the prodromal stage. A review of methods for preclinical and early clinical diagnosis of PD shows that the study of prodromal markers and criteria for the premotor phase of PD will make it possible in the future to significantly change the course of the disease using neuroprotective therapy at the stage preceding the death of a significant number of dopaminergic neurons of the substantia nigra.